Avaliação da qualidade da água do rio Jucu/ES (Brasil), por meio de parâmetros físico-químicos e biológicos - Silva, Taina Turial da (2019)
The Jucu River is one of the main rivers in the state of Espírito Santo (Brazil), because it supplies 25% of the population and is essential to society. The water conditions of the river were studied by analyzing physico-chemical, microbiological and biological parameters, such as: temperature, electrical conductivity, dissolved oxygen, turbidity, total solids, solids dissolved and suspended, biochemical oxygen demand, chemical demand of oxygen, total nitrogen, thermotolerant coliforms and Escherichia coli, trace elements and phytotoxic effect using Lactuca Sativa as a bioindicator. The presence of trace elements Al, Ca, Fe, Mg, Mn, Ni, Zn, Cd, Cr, Cu, Pb and Co were analyzed in river water and sediment. The results of the surface waters were compared with the resolution of the National Council of the Environment (CONAMA) nº 357/05, and the sediments with the resolution of CONAMA nº 420/09, which are for soils. With the application of the water quality index (IQA), the study showed that in the second season water pollution increased due to rainfall, leaving the river with more contaminants. In addition, it was possible to observe that stations JUC01, JUC05 and JUC06 suffer more from anthropic actions due to the high presence of Escherichia coli, which is related to fecal contamination. The chemometry was used to find similarities between the stations analyzed, the results showed formations of groupings the stations, making separations between the of good and regular waters. In relation to trace elements in water, all stations of the Jucu River presented contaminations by dissolved iron, aluminum and manganese in surface waters, being above the allowed limit. In the sediments only JUC02 station in the first campaign was contaminated by Cr, with a concentration of 84.74mg.Kg-1, and the organic matter content in these sediments was related to trace elements in all campaigns, except for JUC04 station had no affinity. And the water samples promoted a stimulating effect on Lactuca Sativa seeds in phytotoxicity tests due to the presence of many nutrients.